Laccase-mediated in situ oxidation of dopa for bio-inspired coloration of silk fabric. Issue 21 (24th February 2017) - Jia, Weini; Wang, Qiang; Fan, Xuerong; Dong, Aixue; Yu, Yuanyuan; Wang, Ping
Abstract : The mechanism of the biological coloration of silk fabric by laccase-mediated in situ oxidation of dopa is revealed. Abstract : Bio-inspired or bionic coloration of fiber assemblies based on chemical oxidation of phenolics has gained more and more attention in recent years. To overcome the challenges of protecting the ecology and environment in textile processes, a novel approach for the coloration of silk fabrics via laccase-mediated in situ oxidation of dopa (dihydroxy phenylalanine) has been investigated in this work. In view of the fact that laccase is able to catalyze the oxidation of benzenediol followed by polymerization to produce strongly colored phenolic polymers, two biological coloration processes of silk fabrics based on in situ oxidation of dopa using laccase were investigated: (i) the adsorption of silk fabrics with dopa, followed by further catalysis of laccase and (ii) the simultaneous laccase-mediated polymerization and coloration of silk fabrics. Dosages of laccase and incubation time were evaluated in order to increase the color depth and fastness of the silk fabrics. The increase in laccase dosage and reaction time allowed improvement in the depth of the final color. The properties of colored silk fabrics were evaluated in terms of UV-protection and color fastness. Finally, the binding of the polymers of dopa with silk fibers was verified by Fourier transform infrared spectroscopy (FT-IR). The silk fabrics treated with laccase/dopa by a one-step process obtained K / S values of 16.935, light fastness of 4–5 level, and UPF of 100+. SEM and AFM observations showed that the surface of silk samples treated with laccase/dopa had numerous small flakes, which can be regarded as the melanin particles of dopa molecules, attached by the grafting reaction. The FT-IR analysis showed that the functional groups on the surfaces of laccase/dopa-treated silk fabrics were changed with the introduction of carbonyl groups. The results of XPS showed that the elemental composition of the surface of laccase/dopa-treated silk fabrics was similar to oral melanin. This dyeing technique could also be extended to the treatments of other types of fibers in textile dyeing and finishing processes.